Effect of Phubbing Behavior on Student Academic Procrastination - Rachman, Ali; Rusandi, Muhammad Arli; Setiawan, Muhammad Andri (Universitas Ahmad Dahlan, 2019)
The purpose of this study was to measure the effect of phubbing behavior on student academic procrastination. This study uses a quantitative approach to the type of correlation research. The instrument used was a 'Generic Scale of Phubbing' developed by Chotpitayasunondh & Douglas, while the academic procrastination scale adopted the scale developed by Hariati. Research subjects were 278 students taken by probability sampling by determining the number of samples using the Isaac and Michael tables. Research analysis using simple regression analysis. The results showed that the behavior of 'phubbing' had a significant effect on academic procrastination. The results of this study contribute to education that phubbing behavior in addition to reducing the quality of relationship satisfaction and personal well-being can also make a habit of academic procrastination, which is will adversely affect students.Keywords: phubbing, academic procrastination, student